Skewed distribution of hypothyroidism in the coastal communities of Newfoundland, Canada. (October 2015) - Sarkar, Atanu; Knight, John C.; Babichuk, Nicole A.; Mulay, Shree
Abstract: Several studies published in the recent past have shown that rising levels of thyroid disrupting chemicals (TDCs) in the environment affect thyroid function in humans. These TDCs are the anthropogenic organic compounds that enter the human body mostly by ingestion and may trigger autoimmune thyroiditis, the most common cause of hypothyroidism. The studies also show the presence of high levels of TDCs in marine animals; therefore, consumption of contaminated seafood might trigger hypothyroidism. So far, there is no readily available population-based data, showing the regional distribution of hypothyroidism cases. We collected administrative data from the Newfoundland and Labrador Centre for Health Information on hospitalizations with hypothyroidism (from 1998 to 2012) in 41 coastal communities of Newfoundland and found that mean hypothyroidism rates of west and south coasts were significantly higher than in the east coast (1.8 and 1.9 times respectively). A one-way analysis of variance was used to test for regional differences in rates. A significant between-group difference in the rate of hypothyroidism was found (F2, 38 = 8.309; p = 0.001). The St. Lawrence River, its estuary and the Gulf of St. Lawrence are heavily polluted with TDCs from industries, their effluents, and urbanization in the Great Lakes Watershed and along the river. Environment Canada has already identified this river along with the Great Lakes Watershed as one of the top TDCs polluted water sources in the country. The west and south coasts are in contact with the Gulf of St. Lawrence. Local marine products are a regular diet of the coastal communities of Newfoundland. Based on these available evidence, we hypothesize the role of TDCs in the rise of hypothyroidism on the western and southern coasts. However, further study will be needed to establish any association between abnormally high rates of hypothyroidism and exposure to TDCs. Highlights: Mean hypothyroidism rates of the west & south coast of Newfoundland are higher than the east coast. Thyroid disrupting chemicals in seafood are believed to be the reason for high rates. The west and south coasts are in contact with the Gulf of St. Lawrence. Gulf of St. Lawrence is heavily polluted with thyroid disrupting chemicals.